A Novel Approach of Using Electrostatic Field to Reduce Thawing Time and Improve Frozen Beef Quality - Grace E. Corrette; Haley J. Jeneske; Sara R. Hene; Linnea A. Rimmer; Larissa A. Koulicoff; Morgan D. Zumbaugh; Travis G. O'Quinn; Scott J. Eilert; Bret Flanders; Michael D. Chao (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:The objective of this study was to evaluate the impact of applying an electrostatic field (EF) on thawing characteristics, such as thawing speed and purge loss, as well as its impact on quality attributes during subsequent aging and retail display of beef. Study Description:Striploins from both sides of USDA Choice carcasses (n = 12) were collected and portioned into four equal parts (n = 48). Portions were vacuum packaged and frozen at -40°F for 14 days and randomly assigned to one of four EF thawing treatments: 0 kV (control), 2.5 kV (EF-2.5), 5 kV (EF-5), and 10 kV (EF-10). Within each EF treatment, half of the striploin portions were thawed in an inside cooler (32°F) and half in an outside cooler (36°F). The thawing process was considered complete when all striploin portions reached 30.2°F. After thawing, striploin portions were weighed and purge was collected for analysis, and portions were fabricated into steaks. One steak was used for histological analysis to assess muscle fiber damage and remaining steaks were vacuum packaged and subjected to either 0 or 14 days of aging. After the aging, steaks were placed on Styrofoam trays, overwrapped with polyvinyl chloride, and retail displayed for either 0 or 7 days. Steaks were evaluated daily for objective color as well as subjective evaluation of discoloration. After completion of the designated aging and display period, steaks were utilized for Warner-Bratzler shear force (WBSF), sarcomere length, lipid oxidation, pH, and myofibrillar protein degradation analysis. Results: There was an increase in purge loss for all EF samples compared to the control in the outside cooler location (P<0.05). Application of EF did not reduce thawing times (P>0.05), with EF-10 taking longer to reach the targeted 30.2°F (P<0.05). All EF treatments reduced purge aerobic plate count (P<0.01) in the outside cooler location. The EF-10 had lower WBSF (P<0.05), and EF-10 samples from the outside cooler location tended to have greater muscle fiber spacing (P= 0.09). For the 0-day aged samples, EF-5 on day 7 resulted in more discoloration than the rest of the treatments (P<0.05). In samples aged for 14 days, the EF-5 and EF-2.5 had less discoloration than the control and EF-10 (P<0.05). When looking at the impact of EF on a* (redness), EF-5 had higher a* values (more redness) than the control and EF-2.5 on days 4 and 5 of retail display (P<0.05). The EF applications did not alter myofibrillar protein degradation, sarcomere length, lipid oxidation, and purge protein concentrations (P>0.05). The Bottom Line:The application of EF during thawing did not reduce purge loss and thawing times but showed potential as an antimicrobial intervention and color stabilizer.
Keywords: beef quality; electrostatic field; frozen; thawing